The importance of education on ethnic-racial relations in higher education (Research, Society and Development, 2023)
This is a qualitative and exploratory research, aimed at presenting the importance of the education of ethnic-racial relations in higher education. It was decided to take the technique proposed by Bardin as a guideline for the analysis of qualitative data, which is widely used in research of a social nature, and adapt it to the reality of the article. In higher education, undergraduate courses are focused on professional training, and within this scenario it is necessary to understand the importance of implementing the National Curriculum Guidelines for Ethnic-Racial Relations and for the Teaching of Afro-Brazilian and African History and Culture (DCN ), since they provide opportunities for the promotion of discussions around blacks and non-blacks, since they provide training based not only on normative instruments, but mainly on education in positive ethnic-racial relations.